Strategi Guru Dalam Penanaman Nilai-Nilai Antikorupsi Pada Anak Kelompok B di TK Kasih Bunda Beringin - Nelly Agustina; Arini Julia Ningsih; Dina Amaria (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Instilling anti-corruption values from early childhood is considered a strategic preventive approach, given that the 5–6 year period is the most intensive phase of character formation. This study aims to analyze the strategies used by teachers to cultivate anti-corruption values in children aged 5–6 years at TK Kasih Bunda Beringin. A qualitative approach with a case study design was employed. Data were collected through passive-moderate participatory observation, semi-structured interviews with three Group B teachers, and document analysis of daily lesson plans from February to March 2026. Data analysis followed the Miles, Huberman, and Saldaña (2014) interactive model, comprising data condensation, data display, and conclusion drawing, with source triangulation and member checks to ensure credibility. The findings reveal ten integrated strategies applied by teachers: habituating honesty, modeling exemplary behavior, storytelling, role-play, reward and consequence systems, discipline habituation, responsibility cultivation, queuing practice, returning peers' belongings, and group cooperation. A distinctive finding is that these strategies do not operate in isolation but form an interconnected pedagogical ecosystem, with teacher modeling as its primary foundation. The study also identifies barriers, including inconsistent home-based habituation and varying individual responses among children. The novelty lies in its pedagogical process perspective, distinguishing it from prior studies that predominantly measure children's behavioral outcomes